Pig production in Vietnam: How to meet emerging demand for food safety - Nguyen Thi Thu Huyen; Pham Van Hung; Ninh Xuan Trung (2016)
This paper aims to present concerns of pork consumers recently from food safety point of view and investigate approaches that assist pig farmers to meet the requirement of safe pork product of consumers. Based on data from the survey in 2013 and 2014 conducted by ILRI and VNUA, various solutions are suggested. In the first place, safe pork value chains is suggested to be set up and upgraded basing on Lifsap project. This ideal is to link GAHP farmers, slaughters and retailers to provide safe pork to consumers. Next, the paper discusses approaches to mitigate pig diseases leading to a reduction in the use of drugs for pig production such as the application of VietGHAP guideline, designing and investing well infrastructure, cleaning pig houses and examined production tools.